Trichobezoars in children: therapeutic complications - A. Mariotto; M. Peretti; G. Scirè; A. Mantovani; S. Zambaldo; E. Pani; F. Saverio Camoglio; L. Giacomello (PAGEPress Publications, 2014)
Trichobezoars are concretions formed by the accumulation of hair or fibers in the gastrointestinal tract, usually associated with underlying psychiatric disorders in females between 13 and 20 years old. Endoscopy, the gold standard for diagnosis, brings some additional advantages: sample taking, size reducing and, rarely, mass removal. This study shows that endoscopy can cause severe complications resulting in a surgical emergency.